IMPORTANCE AND FUNCTIONS OF SPEECH MELODY (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Speech melody, a key component of prosody, plays a vital role in communication, transcending mere conveyance of lexical meaning. It encompasses pitch variation, rhythm, and intonation, which together influence how speech is perceived, interpreted, and emotionally connected. This article explores the importance and diverse functions of speech melody, highlighting its impact on language, emotion, and communication.